2010
DOI: 10.2527/jas.2009-2724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feed flavors and nursery diet complexity on preweaning and nursery pig performance1,2

Abstract: In Exp. 1, 50 sows and their litters were used to determine the effects of adding a feed flavor to the creep diet on the proportion of pigs consuming creep feed ("eaters") and preweaning performance. Sows were blocked according to parity and date of farrowing and allotted to 2 experimental treatments: 1) litters fed a creep diet with no flavor (negative control) or 2) negative control diet with the feed flavor (Luctarom) included at 1,500 mg/kg. Both creep diets contained 1.0% chromic oxide and were offered ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…It was noticed that feed intake was neglectable in the first 2 days after weaning, leading to malaise. Other factors that might have contributed to this lack of performance are the simple composition of the diet (Sulabo et al, 2010), no growth-promoting Cu in the diet (Bikker, Jongbloed, & van Baal, 2016) and low weaning age (Gu, Li, & She, 2002). With regard to the latter, weaning age was 20 days which is not uncommon in batch-farrowing farms with strict planning since it is observed that with modern hyperprolific sows gestation length increases giving an actual weaning age being lower than scheduled.…”
Section: Discussionmentioning
confidence: 99%
“…It was noticed that feed intake was neglectable in the first 2 days after weaning, leading to malaise. Other factors that might have contributed to this lack of performance are the simple composition of the diet (Sulabo et al, 2010), no growth-promoting Cu in the diet (Bikker, Jongbloed, & van Baal, 2016) and low weaning age (Gu, Li, & She, 2002). With regard to the latter, weaning age was 20 days which is not uncommon in batch-farrowing farms with strict planning since it is observed that with modern hyperprolific sows gestation length increases giving an actual weaning age being lower than scheduled.…”
Section: Discussionmentioning
confidence: 99%
“…That the FA2 unfamiliar starter diet was preferred to the standard starter diet with no additive on the day of feed transition suggests that the FA2 has the ability to mask the change of feed and would be efficient to reduce the negative effect of feed neophobia and maintain feed intake during a sudden feed transition. Certain flavors and sensory additives have the ability to mask the negative properties of unpalatable ingredients, which results in increased feed intake and preferences for the flavoring diets in pigs (Baidoo et al, 1986;Tedò et al, 2008;Sulabo et al, 2010;Michiels et al, 2012). Roura et al (2007) also demonstrated the ability of certain aroma to mask the change of feed during a sudden feed transition.…”
Section: Discussionmentioning
confidence: 99%
“…First, in the present study, it is likely that the small number of animals (n = 8) prevented us from finding significant effects on feed intake and piglets' performance. As proposed by Sulabo et al (2010), it is likely that a great individual variation in palatability perception might also be responsible for the lack of systematic preferences. We assume that repeating the experiment on a larger number of animals would enable us to tackle this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, piglets are early-weaned around three weeks of age in Brazil, a fact that requires attention due to their nutritional requirements and digestive system immaturity. The composition of piglet diets is altered at weaning, once milk is replaced by a solid diet, predisposing animals to nutritional stress which may result in feed intake reduction, poor digestibility, and diarrhea (Sulabo et al, 2010). The reduced secretion of hydrochloric acid by the piglet's stomach and the limited production and activity of pancreatic and intestinal enzymes are also an issue of concern (Heo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%